Role of the Digital Economy and Its Impact on Indonesia's Economic Growth (Journal of Business and Management, 2022)
Economic digitization brings various changes, with the digital economy at least providing many benefits, therefore, digital economic transformation should be used as an alternative solution as an engine of new economic growth. This study examines the real role of the digital economy and economic growth in Indonesia. The regression model was applied to a data panel covering four variables from 2016 to 2021. The ordinary least square model showed a better and more based estimate than the one adjusted for this study. In addition, the digital economy variable in this study has a positive impact on economic growth in Indonesia, especially during the COVID-19 pandemic. This evidence implies that the digital economy has a positive and significant impact on economic growth in Indonesia.Keywords: Economic growth, digital economy, GDP